Pengaruh Konsentrasi Tapioka terhadap Karakteristik Kimia dan Organoleptik Kerupuk Sawi (Brassica chinensis var Parachinensis) - Umanahu, Irfan; Polnaya, Febby J; Breemer, Rachel (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to determine the best concentration of tapioca against the chemical and organoleptic characteristics of mustard crackers. The study design used a one-factor complete randomized design with four levels of treatment for adding tapioca flour concentrations. The levels of this treatment are tapioca concentrations 60, 80, 100, and 120%. The parameters analyzed are water content test, ash content test, fat content test, fiber content test, and organoleptic test of taste, color, aroma, crunchy, and overall). The results showed that mustard crackers had a water content of 5.14 to 6.79%, ash content of 1.48 to 1.76%, fat content of 11.90 to 15.10%, and fiber content of 7.55% to 9.50%. Panelists, on average, liked mustard crackers treated with 100% tapioca concentration for taste, color, aroma, and crispness. The hedonic quality of mustard crackers showed the value of mustard taste, green color, mustard aroma, and crunchiness. Overall, the panelists liked the mustard crackers with 100% tapioca concentration.